Innovative Approaches to Online Language Instruction: International Perspectives (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The acquisition of foreign languages has long been a central concern in linguistic pedagogy. Recent advancements in Artificial Intelligence (AI) integration have revolutionized English language teaching methodologies, creating new paradigms for instructional delivery and learning processes. This study examines implementation challenges while proposing evidence-based recommendations for developing linguistic competence in English Language Teaching (ELT). Through systematic analysis of competency-based approaches and prevalent instructional methods in digital environments, the research synthesizes both domestic and global best practices, highlighting significant developments in this evolving discipline. The present meta-analysis of optimal distance language education strategies provides critical perspectives on modern pedagogical approaches.